SCHEMES AND METHODS OF FINANCING REAL ESTATE TRANSACTIONS - V. Busov (Вестник университета)
The article a description and suggestions for use in the modern world, some developed in Russia, which showed its effectiveness and the forgotten schemes of financing transactions with real estate; the necessity in parallel with the currently operating duplex in the country of formation and development of single-level diagram of the system of mortgage lending, based on target savings, and the feasibility of the state subsidizing the borrower's down payment and no payments on mortgage loan rate.